2020
DOI: 10.1126/science.aay2494
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum–associated degradation regulates mitochondrial dynamics in brown adipocytes

Abstract: The endoplasmic reticulum (ER) engages mitochondria at specialized ER domains known as mitochondria-associated membranes (MAMs). Here, we used three-dimensional high-resolution imaging to investigate the formation of pleomorphic “megamitochondria” with altered MAMs in brown adipocytes lacking the Sel1L-Hrd1 protein complex of ER-associated protein degradation (ERAD). Mice with ERAD deficiency in brown adipocytes were cold sensitive and exhibited mitochondrial dysfunction. ERAD deficiency affected ER-mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 64 publications
4
107
0
Order By: Relevance
“…ER‐associated proteins, such as Mff, Fis1, MiD49, and MiD51 function as receptors to mediate the process 13,54 . A recent finding further demonstrates that ER‐associated protein degradation (ERAD) regulates directly the dynamics of mitochondria 55 . Here, we report that DRP1 translocates onto ER and facilitate dissociation of newly formed LDs from ER.…”
Section: Discussionmentioning
confidence: 54%
“…ER‐associated proteins, such as Mff, Fis1, MiD49, and MiD51 function as receptors to mediate the process 13,54 . A recent finding further demonstrates that ER‐associated protein degradation (ERAD) regulates directly the dynamics of mitochondria 55 . Here, we report that DRP1 translocates onto ER and facilitate dissociation of newly formed LDs from ER.…”
Section: Discussionmentioning
confidence: 54%
“…Another known Drp1 receptor, Fis1, has been shown in C. elegans to enter into a complex containing Drp1, Mff, and ER proteins at the ER-mitochondrial interface during stimulation of mitophagy (112). Strikingly, it is recently reported that endoplasmic reticulum-associated degradation (ERAD), an ER quality control mechanism, regulates mitochondrial dynamics (130). Additionally, in human cells, a subset of ER-mitochondria contacts spatially couple mtDNA replication with downstream mitochondrial division (131).…”
Section: Roles Of the Endoplasmic Reticulum In Mitochondrial Dynamicsmentioning
confidence: 99%
“…A recent study has implicated components of the ER-associated degradation (ERAD) quality control pathway in regulating mitochondrial dynamics via ER-mitochondria contacts [ 50 ]. In brown adipocytes, loss of the ER-resident ERAD protein Sel1L prevents the mitochondrial fission usually stimulated by cold stress, resulting in enlarged ‘megamitochondria’ with impaired metabolic functions.…”
Section: Mitochondrion-organelle Interactions and Their Physiologicalmentioning
confidence: 99%
“…* MCS components listed are those mentioned in the text; this is not a complete list of all MCS components identified so far. Organelles (MCS) MCS components* Physiological role References Mitochondria – endoplasmic reticulum SigmaR1 (MITO), SEL1L (ER) Regulation of mitochondrial fission [ 50 ] Spire1C (MITO) – INF2 (ER) tether [ [45] , [46] , [47] ] IP 3 R (ER) – GRP75 – VDAC (MITO) tether Transfer of Ca 2+ between ER and MITO; Ca 2+ signalling via MITO-ER contacts [ 56 , 57 ] PDZD8 (MITO/LYS?) – Unknown protein (ER) tether Dendritic Ca 2+ homeostasis in mammalian neurons?…”
Section: Introductionmentioning
confidence: 99%